Amaryllidaceae Alkaloids as Potential Glycogen Synthase Kinase-3β Inhibitors - Hulcová, Daniela; Breiterová, Kateřina; Siatka, Tomáš; Klímová, Kamila; Davani, Lara; Šafratová, Marcela; Hošťálková, Anna; De Simone, Angela; Andrisano, Vincenza; Cahlíková, Lucie (Molecules (Basel, Switzerland), 2018)
Glycogen synthase kinase-3β (GSK-3β) is a multifunctional serine/threonine protein kinase that was originally identified as an enzyme involved in the control of glycogen metabolism. It plays a key role in diverse physiological processes including metabolism, the cell cycle, and gene expression by regulating a wide variety of well-known substances like glycogen synthase, tau-protein, and β-catenin. Recent studies have identified GSK-3β as a potential therapeutic target in Alzheimer´s disease, bipolar disorder, stroke, more than 15 types of cancer, and diabetes. GSK-3β is one of the most attractive targets for medicinal chemists in the discovery, design, and synthesis of new selective potent inhibitors. In the current study, twenty-eight Amaryllidaceae alkaloids of various structural types were studied for their potency to inhibit GSK-3β. Promising results have been demonstrated by alkaloids of the homolycorine-{9-O-demethylhomolycorine (IC50 = 30.00 ± 0.71 µM), masonine (IC50 = 27.81 ± 0.01 μM)}, and lycorine-types {caranine (IC50 = 30.75 ± 0.04 μM)}.
Keywords: Amaryllidaceae alkaloids; masonine; Inhibitory Concentration 50; Amaryllidaceae Alkaloids; Protein Kinase Inhibitors; Drug Evaluation, Preclinical; kinasa glykogensynthasy 3beta; caranine; Humans; inhibiční koncentrace 50; preklinické hodnocení léčiv; Glycogen Synthase Kinase 3 beta; 9-O-demethylhomolycorine; lidé; alkaloidy amarylkovitých; inhibitory proteinkinas; Alzheimer’s disease; glycogen synthase kinase-3β